Association of growth hormone gene receptor polymorphism with production traits in Jamunapari goat - SINGH, PALLAVI; SINGH, M K; ROUT, P K; DIGE, M S (The Indian Journal of Animal Sciences, 2018)
Genetic polymorphism for GHR gene was carried out in Jamunapari kids by Polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP). Blood samples were collected from 200 kids for isolation of genomic DNA. The exon 1A (210 bp fragment), exon 10 (342 bp fragment) and 5’ non-coding region (318 bp fragment) of GHR gene were amplified and digested with MspI, AluI and NsiI restriction endonuclease, respectively. PCR-RFLP analysis for 5’ non-coding region revealed monomorphic pattern while exon 1A and exon 10 of GHR were polymorphic. The frequency of A and T alleles was 0.54 and 0.46, respectively, and frequency of three genotypes (AA, AT and TT) was 0.17, 0.74 and 0.09, respectively at locus exon 1A of GHR. The frequency of A and G allele for exon 10 was 0.53 and 0.47, and frequency of three genotypes (AA, AG and GG) was 0.16, 0.74 and 0.10, respectively. The genotype AG was associated with higher body weights at different growth stages. The goats with AG genotype were heavier to AA and GG genotypes by 4.91 and 42.85% at birth; 8.59 and 13.30% at 6 months; 8.02 and 17.25% at 9 months and 7.11 and 16.11% at 12 months, respectively. The locus was also a significant source of variation for biometrical traits (body weight, body length, heart girth) at different ages. AG genotype could be used as marker in selection for higher body weights in Jamunapari goats.